THE ROLE OF PSYCHOLOGICAL CAPITAL IN PREDICTING AFFECTIVE COMMITMENT AMONG GENERATION Y - Endro Puspo Wiroko (Psibernetika, 2019)
ABSTRACT. The present study investigated the role of psychological capital to affective commitment. Affective commitment is employee’s emotional attachment to, identification with, and involvement in the organization. Psychological capital is positive psychological state of development and is characterized by self efficacy, optimism, hope, and resiliency. This is the first study to examine the role of psychological capital on affective commitment by using generation Y in Jakarta as participants. They were 176 male and female employees who were varied in age, job level, employment status, tenure, educational background,  and work location. Data was gathered by using two measures: psychological capital and affective commitment scale. Interestingly, this study revealed that psychological capital significantly predict affective commitment in statistical point of view but not in practical implication. Regression analysis reported that psychological capital contribute only 2% to affective commitment among Indonesian generation Y.Keywords:  affective commitment, psychological capital, generation Y ABSTRAK. Penelitian ini bertujuan untuk mengetahui peran modal psikologis terhadap komitmen afektif. Komitmen afektif adalah kelekatan emosional, identifikasi, dan keterlibatan karyawan dalam organisasi. Modal psikologis adalah kondisi positif perkembangan psikologis yang ditandai dengan efikasi diri, optimisme, harapan, dan resiliensi. Penelitian ini menjadi studi pertama yang menguji modal psikologis sebagai prediktor dari komitmen afektif dengan menggunakan generasi Y di Jakarta sebagai partisipan. Mereka adalah 183 karyawan pria dan wanita yang bervariasi dalam hal usia, tingkat jabatan, status karyawan, masa kerja, latar belakang pendidikan, dan lokasi kerja. Data diambil dengan menggunakan dua alat ukur: skala modal psikologis dan skala komitmen afektif. Menariknya, penelitian ini menunjukkan bahwa modal psikologis dapat memprediksi komitmen afektif dalam sudut pandang statistik tetapi tidak dalam implikasi praktis. Analisis regresi menunjukkan bahwa modal psikologis hanya memberikan kontribusi sebesar 2% terhadap komitmen afektif pada generasi Y di Indonesia. Kata kunci: komitmen afektif, modal psikologis, generasi Y